PENDUGAAN GALAT BAKU DENGAN METODE BOOTSTRAP MENGGUNAKAN R LANGUAGE - Uyanto, Stanislaus S. (Majalah Ilmiah Matematika Komputer, 2005)
A summary statistics such as are often the first outputs of data analysis. Then next thing we want to know is the accuracy of The most common measure of an estimator's accuracy is the standard error. The bootstrap method is a computer based method fo assigning measures of accuracy to statistical. estimates. In this writing we will show how to obtain the standard error of a statistic using the bootstrap.Â Kata kunci : statistic. bootstrap, estimate, standard error, galat baku